ANDALALIN PEMBANGUNAN RUKO 88 BERLIAN COMMERCIAL ESTATE DI KOTA TANGERANG - Hari Andoyo; Sri Yuniarti (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2020)
Changes in land use in an area will cause new attractions and trip generation which usually will potentially cause problems in the surrounding traffic. The construction of Ruko 88 Berlian Commercial Estate in Tangerang City is also a change in land use from vacant land to a center of activity in the form of shop houses. Thus, a traffic impact analysis is needed to find out the potential impacts that affect the road network system around the construction site. The study conducted several traffic surveys such as surveys of road and intersection inventory, enumeration of traffic on roads and intersections, calculation of trip generation and travel attraction, parking etc. All surveys were conducted to measure the performance of the road network at the study site. The method used at the time of the analysis refers to the Indonesian Highway Capacity Manual, the Four Step Model Method, and some guidelines related to parking. After analyzing it in various stages, it was concluded that Ruko 88 Berlian Commercial Estate provides a traffic impact during the construction and operational processes by generating new trip generation of 44 pcu / hour and new travel attractions of 45 pcu / hour. From this, the performance of the road network around the location has decreased, marked by an increase in V / C ratio and traffic density and a decrease in speed. To overcome the impact of the traffic the recommended mitigations include making entry and exit access designs, structuring parking, installing road equipment facilities etc. From the results of the analysis, mitigation is quite able to reduce the impact of traffic caused by Ruko 88 Berlian Commercial Estate